Dosimetría de las penas en el código orgánico integral penal, artículo 170 - Muriel Chacón, Héctor Hugo (2016)
Treatment docimetry penalties under Article 170 of the Code of Criminal Integral and affected by the content of article 13 of the same Code, by reason of being disproportionate, which violates the principle of proportionality between the act is essential injurídico and the penalty to be imposed, as provided in the Constitution of our country. The problem is not addressed only from the point of view of the penalty but also the drafting and interpretation of the rule, since it is one of those open-ended, where it can fit any type of misconduct that approaches or resembles basic concept of sexual abuse, which contracted specific provisions of the Code of Criminal Integral, such as the prohibition of extensive interpretation or use of the analogy, what is known as the creation of new offenses or crimes. According to studies sexual offenses are the most abundant in the social live, and the sexual precocity of children and adolescents and technological advances that provide distorted information and lewd messages that negatively influence the psychosexual development of the human race. All this forces the Ecuadorian legislature to be more cautious with the criminalization of offenses of sexual abuse, not being recommended, technical anti legally, widespread violations of sexual abuse, as all are not equally dangerous, negative psychological impact the victim, nor obey the object of the sentence.